Efektivitas Metode Flashcard dalam Pembelajaran Kosakata Komunikasi Bahasa Jepang : The Effectiveness of the Flashcard Method in Learning Japanese Communication Vocabulary - Galuh Wismadewi; Ary Susandi; Putu Rusanti; Novi Suryati; Maya Cyntia (ITScience (Information Technology and Science), 2025)
This study aimed to investigate the effectiveness of the flashcard method for learning vocabulary related to pre- and post-anaesthesia communication in Japanese for anesthesiology nursing students. Vocabulary mastery is crucial in medical interactions, especially in healthcare services for Japanese patients in international hospitals. The flashcard method was chosen for its ability to improve vocabulary retention and comprehension through an interactive, visual, and verbal approach. The research used a quantitative, pre-experimental, one-group pretest-posttest design, involving only one experimental class without a comparison or control group. The research instruments included a vocabulary mastery test and a questionnaire to measure students' responses. The results showed a significant increase in vocabulary mastery for pre- and post-anaesthesia communication in the group using the flashcard method. In addition, students responded positively to flashcards, finding them interesting, easy to use, and helpful for understanding the meaning of medical vocabulary in context. This study concluded that the flashcard method was effective in improving vocabulary mastery for medical communication for anesthesiology nursing students.